Pollinator Insects and their Impact on Crop Yield of Mustard in Kusma, Parbat, Nepal - Subedi, Narayan; Subedi, Indra Prasad (Journal of Institute of Science and Technology, 2019)
The diversity of insect pollinators and their impact on crop yield of mustard were studied in Kusma, Parbat, Nepal from December 2018 to April 2019 in four blocks with each having 12 m2 areas. Two plots; treatment and control, were established in each block. Insect diversity was observed from 8 to 16 hrs, with the interval of an hour for three consecutive months (Jan-Feb). Eighty mustard plants were randomly selected, 40 from each plot just before flowering to find the impact of insect pollination on crop yield and these selected plants were examined for various qualitative and quantitative parameters. Altogether 16 species of pollinator insects belonging to five orders and nine families were recorded. Hymenoptera (36 %) was the most abundant order visiting mustard flowers followed by Diptera (34 %), Coleoptera (17 %), Lepidoptera (12 %) and Heteroptera (1 %). The most abundant family was Apidae (35.64 %), followed by Syrphidae (31.84 %). Apis cerana and Eristalis sp. were the most important pollinator insects of mustard. Seven species were found foraging both on pollen and nectar, four species foraging only on nectar and remaining five as casual visitors. The peak foraging activities of majority of the insects were observed between 12 hr to 14 hr. A significant difference was observed in the number of pods (59.80 ± 1.967 and 70.47 ± 2.431), fruit set (70.55 ± 1.362 and 80.94 ± 0.638), number of seeds per pods (16.70 ± 0.248 and 19.30 ± 0.330), diameter of seed (0.133 ± 0.2547 and 0.275 ± 0.0051) and weight of 100 dry seeds (0.33 ± 0.058 and 0.48 ± 0.023) in control and treatment plots whereas, the difference was non-significant in case of pod length between control and treatment plots (P=0.163).